2021
DOI: 10.3389/fpubh.2021.661279
|View full text |Cite
|
Sign up to set email alerts
|

Does Economic Overheating Provide Positive Feedback on Population Health? Evidence From BRICS and ASEAN Countries

Abstract: This paper explores the relationship of real GDP per capita with cancer incidence applying panel threshold regression model in BRICS and ASEAN countries. The empirical results highlight that the business cycle has an inverted-U correlation with population health indicators and a non-linear single threshold effect. In BRICS countries, the health-promoting effect of economic growth is significantly weaker when exceeding the threshold. Similarly, economic growth in ASEAN countries, even worsens population health,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…Bai et al ( 23 ) uses the panel data of 29 regions in China to explore the impact of EPU on medical expenditure and finds that EPU has a positive spatial spillover effect on medical expenditure. Su et al ( 24 ) found that there was an inverted U-shaped correlation between economic growth and health, and the health promotion effect of economic growth decreased significantly when it exceeded the threshold.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bai et al ( 23 ) uses the panel data of 29 regions in China to explore the impact of EPU on medical expenditure and finds that EPU has a positive spatial spillover effect on medical expenditure. Su et al ( 24 ) found that there was an inverted U-shaped correlation between economic growth and health, and the health promotion effect of economic growth decreased significantly when it exceeded the threshold.…”
Section: Literature Reviewmentioning
confidence: 99%
“…High-speed railway, with its high speed and wide coverage, can meet the need for efficient and convenient transport. As a transport infrastructure with large-scale investment, high-speed railways have a close relationship with economic development and national living standards, and also play an important role in improving the health care conditions of cities along the route (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large and growing body of literature has investigated the determinants of healthcare expenditure, such as business cycles ( 2 ), economic overheating ( 3 ), economic activity ( 4 ), economic crisis ( 1 , 5 ), and other factors ( 6 – 10 ). The most studied determinant is economic growth, which is an important demand-side driver of healthcare expenditure ( 2 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Estimation results of robustness tests.This table presents the robustness test results; Columns(1)(2)(3) are the results of the alternative measure of healthcare expenditure (Out_exp) based on the three spatial weight matrices, respectively; Columns(4)(5)(6) are the results of the alternative measure of EPU (EPU2) based on the three spatial weight matrices; Column(7) is the result of the endogenous test using the GMM method; The results of control variables are consistent with those in Table5, and we do not report them in this table due to space limitations; ***p < 1%, **p < 5%, and *p < 10%, respectively; t-statistics value in brackets.area (the coefficient is −0.0571, and the corresponding tvalue is −1.22). The above results indicate that EPU has significant positive effects on healthcare expenditure in the eastern and central areas, while the effects are not significant in the western area.…”
mentioning
confidence: 99%